2020
DOI: 10.1111/ajt.15571
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type I receptor agonistic autoantibodies are associated with poor allograft survival in liver retransplantation

Abstract: Angiotensin II type I receptor (AT1R) agonistic autoantibodies (AT1R-AA) are detrimental to kidney transplantation. Early studies suggested a similar negative effect in primary liver transplantation. Here, we studied AT1R-AA in a retrospective cohort of 94 patients who received a second liver transplant to determine their prevalence and effects. The concentrations of preformed AT1R-AA before transplantation were higher (p=0.019) in the 48 patients who lost their liver grafts than in the 46 patients whose graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…In a previous study of 94 patients who underwent a second LT, we found that preformed Angiotensin II Type I Receptor agonistic autoantibodies (AT1R-AA) were associated with reduced allograft survival. 25 Specifically, 16/22 (72.7%) patients with strong AT1R-AA (>40 U/ml) had lost their second allografts. However, only one-third (16/48) of patients who lost their second liver allograft had strong AT1R-AA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of 94 patients who underwent a second LT, we found that preformed Angiotensin II Type I Receptor agonistic autoantibodies (AT1R-AA) were associated with reduced allograft survival. 25 Specifically, 16/22 (72.7%) patients with strong AT1R-AA (>40 U/ml) had lost their second allografts. However, only one-third (16/48) of patients who lost their second liver allograft had strong AT1R-AA.…”
mentioning
confidence: 99%
“…Therefore, the primary aim of this study was to determine if there were other preformed autoantibodies that could explain the difference in graft survival observed in our previous study. 25 To do that, we retrospectively tested a multiplex panel of 33 autoantibodies in pre-operative sera of the same cohort of patients who underwent a second LT.…”
mentioning
confidence: 99%
“…The presence of AT 1 R antibodies is also associated with higher rates of AMR in intestinal and multivisceral transplantation (Gerlach et al., 2017). Recently, in redo liver transplantation, high levels of AT 1 R antibodies have been associated with increased risk of graft loss (Xu et al., 2019). Furthermore, in paediatric liver transplantation, higher levels of AT 1 R antibodies were found in patients with advanced fibrosis (Ohe et al., 2014).…”
Section: Antibodies Against Angiotensin II Type 1 Receptor (At1r)mentioning
confidence: 99%
“…It is important to note that it is the altered pro‐inflammatory content of exosomes (cytokines, chemokines, and costimulatory molecules) released from injured and activated tissues that appears to potentiate HLA and non‐HLA antibody development. Therefore, it will be important to determine how the context of events associated with vascular insults such as ventricular assist device surgery vs liver rejection potentiate non‐HLA antibodies with noninjurious vs injurious potential, respectively 6,7 …”
Section: Figurementioning
confidence: 99%
“…Therefore, it will be important to determine how the context of events associated with vascular insults such as ventricular assist device surgery vs liver rejection potentiate non-HLA antibodies with noninjurious vs injurious potential, respectively. 6,7 New tools in the laboratory hold great promise for understand- New tools for recognizing different phenotypes of non-HLA antibody-mediated injury, particularly subclinical injury, will be complicated given the functional heterogeneity of ECs across vascular beds and the nonimmune factors that contribute to EC dysfunction.…”
mentioning
confidence: 99%